Foul play Off side - Palmer, Tom (Puffin Books : [distributor] Penguin Books Ltd London, 2010)
When Danny Harte finds out there's been an anonymous foreign buy-out of his favorite club, City, he's furious - the fans were about to buy it themselves. The club is being secretive and Danny is determined to find out what's going on - until he's caught staking out the club by the police and cautioned. His parents are furious, and his friends too